Effectiveness of injury prevention programs on developing quadriceps and hamstrings strength of young male professional soccer players - Daneshjoo, Abdolhamid; Rahnama, Nader; Mokhtar, Abdul Halim; Yusof, Ashril (De Gruyter Open, 2013)
Muscular strength is an important factor which is crucial for performance and injury prevention in most sports. The purpose of this study was to evaluate the effects of the FIFA's Medical Assessment and Research Centre 11+ and HarmoKnee injury prevention programs on knee strength of young professional male soccer players. Thirty-six soccer players (age: 18.9 ± 1.4 years) were divided equally into three groups; the 11+, HarmoKnee and control groups. The programs were performed for 24 sessions. Hamstring and quadriceps strength was measured using the Biodex System 3 at 30°, 60° and 90° of knee flexion. The 11+ increased quadriceps strength in the dominant leg by 19.7% and 47.8% at 60°and 90° knee flexion, respectively, and in the non-dominant leg by 16%, 35.3% and 78.1 % at 30°, 60° and 90° knee flexion, respectively. The HarmoKnee group, however, showed increased quadriceps strength only at 90° i.e., by 85.7% in the dominant leg and 73.8% in the non-dominant leg. As for hamstring strength, only the 11+ group demonstrated an increment by 24.8% and 19.8% at 30° and 60° knee flexion in the dominant leg, and in the non-dominant leg, by 28.7% and 13.7% at 30° and 60° knee flexion, respectively. In conclusion, both warm-up programs improve quadriceps strength. The 11+ demonstrated improvement in hamstring strength while the HarmoKnee program did not indicate any improvement. We suggest adding eccentric hamstring components such as Nordic hamstring exercise to the HarmoKnee program in order to enhance hamstring strength.